Childhood lupus vulgaris after Bacillus Calmette-Guérin vaccine - Sarah Hamdy Soliman; Amany El Agamy El-Samadony; Ghada F Rezk Hassan; Rania Ahmed El-Tatawy; Nesrin Sabry Gomaa (Wolters Kluwer Medknow Publications, 2023)
Lupus vulgaris (LV) is a cutaneous mycobacterial tuberculosis infection that is transmitted through lymphatic routes, hematogenous routes, or exogenous inoculation. It is infrequently reported after the Bacillus Calmette-Guérin (BCG) vaccine. In this report, we present a young child with LV at her BCG vaccine injection site as well as distant lesions of the chin.